EVALUASI IMPLEMENTASI PROGRAM UNIVERSAL HEALTH COVERAGE UNTUK MENGATASI MASALAH KESEHATAN MASYARAKAT KURANG MAMPU DI KOTA SEMARANG - Muhammad Luthfi; Puji Astuti (Journal of Politic and Government Studies, 2019)
Health insurance is a very important requirement for the society, but still can be found that not all people have health insurance, this is due to the existence of several social problems, one of which is poverty, Wagstaff in his book explaining that the level of poverty is inversely proportional to the level of health, if in one area the poverty level is high then the level of public health will definitely be low. In order to improve the quality of health, the City of Semarang implemented a Universal Health Coverage Program targeting the people of Semarang who do not have health insurance.This study uses qualitative research methods supported by qualitative formative evaluation theory and implementation theory, the site of this study is Semarang City Health Office and the people of Semarang who have become Universal Health Coverage participants.The results of the study obtained from field related to the implementation of the Universal Health Coverage program since the beginning of the program have been running until now that the program has run quite well, but still needed some improvements in the context of supervision and ways of socialization to be more effective and efficient.Keywords : Universal Health Coverage, Implementasi Program, Evaluasi Program